Etude des propriétés géotechniques des sols contaminés - Younes BELATRACHE, Habib BELBECIR; Enca/ MEDDAH Abdelaziz (University of M'sila, 2023)
The geotechnical properties of soils polluted by petroleum derivatives (such as diesel) are significantly altered after contamination. However, different treatment methods can improve the properties of these soils. This study examines the effect of diesel contamination of clay taken from the region of Sidi Hadjres, Wilaya of M’sila. The experimental program undertaken includes compaction and compressive strength tests. The tests were carried out on natural soil (without contamination) and soil contaminated with diesel in different concentrations (3.6, and 9%). The study also considers the potential to improve the mechanical performance of contaminated clay by its treatment with sand and lime. The results obtained showed that diesel modifies the mechanical properties of this clay. However, adding lime and/or sand to contaminated soils significantly contributes to regaining the natural properties of the soil with a low lime content